Substrate system outperforms water-culture systems for hydroponic strawberry production - George Kerrigan Hutchinson; Lan Xuan Nguyen; Zilfina Rubio Ames; Krishna Nemali; Rhuanito Soranz Ferrarezi (Frontiers in Plant Science)
Strawberries (Fragaria × ananassa) are a globally cultivated fruit crop known for their economic significance and versatility in both fresh markets and processed food industries. Their high consumer demand and market value contribute to substantial profitability for producers. In recent years, due to increasing costs of production and occurrence of extreme weather events, the use of controlled environment agriculture (CEA) and hydroponics for strawberry production has become popular in several Asian, European, and American countries. There are two main types of hydroponic systems: substrate- and water-culture. Substrate-culture systems are the common choice for CEA strawberry production, whereas water-culture systems are usually used for crops like leafy greens and herbs. Both systems have been independently studied for CEA strawberry production, but direct comparisons between them are still limited. The objective of this study was to compare the performance of substrate and water-culture systems for CEA strawberry production regarding yield and resource use efficiencies. ‘Florida Brilliance’ and ‘Florida Beauty’ strawberries were grown in a greenhouse in one substrate-culture, with plants grow in soilless media, and three water-culture systems: nutrient film technique (NFT), vertical tower (stacked nutrient flow), and aeroponics (nutrient misted roots). The system inputs (water, energy, and area) and outputs (yield, biomass, etc.) were quantified during the 129-day experiment. Fruit yield was used to calculate water (WUE), energy (EUE), and area (AUE) use efficiencies. Based on yield and resource use efficiencies, the substrate system performed the best, with the vertical tower system also showing promising performance. The results of this experiment can help growers understand the tradeoffs between hydroponic systems to maximize both profits and sustainability for CEA strawberry production.